Pengaruh Latihan Power Tungkai terhadap Kemampuan Tendangan Dollyo dalam Cabang Olahraga Taekwondo pada Atlet SKTC Dojang Sea - Mieke Mumekh; Jeanne Malonda; Claudia Triana Rorimpandey (STIKES Columbia Asia Medan, 2024)
The problem in this study is whether there is an effect of leg power training on dollyo's kicking ability in taekwondo in SKTC Dojang Sea athletes. The purpose of the study was to determine the extent of the effect of leg power training on dollyo's kicking ability in taekwondo in SKTC Dojang Sea athletes. The research hypothesis of agility training is the influence of limb power training on dollyo's kicking ability in taekwondo. The research method used is the experimental method. The population in this study was all SKTC Dojang Sea athletes totaling 16 athletes, the sample was the entire population divided into two groups, namely 8 experimental group athletes and 8 control group athletes. The data collection instrument